2022
DOI: 10.1093/gastro/goac082
|View full text |Cite
|
Sign up to set email alerts
|

Re-recognition of BMPR1A-related polyposis: beyond juvenile polyposis and hereditary mixed polyposis syndrome

Abstract: Background Bone morphogenetic protein receptor type 1A (BMPR1A) is responsible for two individual Mendelian diseases: juvenile polyposis syndrome and hereditary mixed polyposis syndrome 2, which have overlapping phenotypes. This study aimed to elucidate whether these two syndromes are just two subtypes of a single syndrome rather than two isolated syndromes. Methods We sequenced the BMPR1A gene in 186 patients with polyposis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Typical juvenile polyps were only found in 3 patients, and adenomatous polyps, mixed polyps, and CRC were found in other patients. Gao et al reported a patient with BMPR1A c.949_952 delCTCT, p.Leu317Metfs à 4 (the same as the one reported by Zhao et al 73 ) with adenomatous polyps as phenotype, which was clinically misdiagnosed as FAP. 74 Pathogenic variant of SMAD4 leads to juvenile polyposis (JPS) and hereditary hemorrhagic telangiectasia, and 40% of patients may also have thoracic aortic disease.…”
Section: Juvenile Polyposis Syndromementioning
confidence: 63%
See 1 more Smart Citation
“…Typical juvenile polyps were only found in 3 patients, and adenomatous polyps, mixed polyps, and CRC were found in other patients. Gao et al reported a patient with BMPR1A c.949_952 delCTCT, p.Leu317Metfs à 4 (the same as the one reported by Zhao et al 73 ) with adenomatous polyps as phenotype, which was clinically misdiagnosed as FAP. 74 Pathogenic variant of SMAD4 leads to juvenile polyposis (JPS) and hereditary hemorrhagic telangiectasia, and 40% of patients may also have thoracic aortic disease.…”
Section: Juvenile Polyposis Syndromementioning
confidence: 63%
“…56 Zhao et al recently published the results of a trial of BMPR1A-associated polyps in Chinese population. 73 A total of 166 patients with colorectal polyps and 20 patients diagnosed with CRC before age 50 were enrolled. Patients with positive genetic tests are evaluated according to the corresponding clinical diagnostic criteria for JPS or HMPS.…”
Section: Juvenile Polyposis Syndromementioning
confidence: 99%
“…У носителей патогенного варианта гена BMPR1A редко встречается поражение верхних отделов ЖКТ, а проявления заболевания в толстой кишке варьируют от наличия смешанного полипоза (в кишке определяются как ювенильные, так и аденоматозные полипы) до выявления колоректального рака на фоне отсутствия полипов в толстой кишке [38]. Некоторые авторы даже выделяют отдельный вид полипозного синдрома -наследственный смешанный полипозный синдром (hereditary mixed polyposis syndrome -HMPS), отмечая при этом его обусловленность патогенными вариантами гена BMPR1A [39,40].…”
Section: клинические проявления у пациентов с патогенным вариантом ге...unclassified